The Role and Place of Fusionism in School Geometry Education - G. A. Klekovkin (Russian State Vocational Pedagogical University, 2015)
The paper deals with the issue of succession in school geometry education. By the analysis and synthesis of the integrative experience of the plane and spatial geometry teaching, it has being substantiated that the application of fusionism elements can provide the effective instrument for implementing the vertical content and process succession in geometry teaching. By means of the activity approach it is being proved that the fusion teaching of planimetry and stereometry in elementary school facilitates the development of children's learning and cognitive skills. Using fusionism at the final years of Secondary School promotes the school leavers' readiness for studying general spatial geometry in the system of higher education. The study is addressed to developers of the school mathematical educational standards, authors of school geometry manuals and geometry teachers.